Response to Letter to the editor: ‘European guidelines for topical PDT part 1. JEADV 2013;27:536–544' DOI: 10.1111/jdv.12258 - C.A. Morton; R.‐M. Szeimies; A. Sidoroff; L.R. Braathen (Journal of the European Academy of Dermatology and Venereology, 2015)
BACKGROUND: This first part of the S2k guidelines is an update of the 2015 S1 European guidelines based on the structured assessment of clinically relevant topics by the panel of experts. It is complemented by Part 2, which deals with treatments. OBJECTIVES: These guidelines aim to provide the generalist with expert guidance regarding clinically relevant topics such as, for example, diagnosis, clinimetrics and comorbidities. METHODS: The S2k level guidelines signify that they are based on expert consensus. This includes all the topics touched upon, all selected after a Delphi procedure among the experts/authors and edited into a coherent whole providing an overview of the subject. Certain passages have been adopted without changes from the previous version. The treatment of the disease and potential treatment complications are not included, being beyond the scope of this guidelines part. RESULTS: Since the S1 guidelines publication, the literature on HS management has grown rapidly, enabling the current revision. The expansion of the guideline is evident and signifies a major leap forward in HS management. CONCLUSIONS: The first part of the guideline for HS provides a consensus-based advice aimed at improving the health care of patients with HS at a generalist level through expert advice.